Intangible Capital: Complement or Substitute in the Creation of Public Goods? - Martin Gornig; Alexander Schiersch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper tests whether intangible capital is a substitute or, to some degree, a complement to standard inputs in the production process. The analysis is conducted for public sectors in which governmental institutions are directly responsible both for efficiently producing public goods and for investing in new production factors. The results reveal that intangible capital is a relevant input factor in the production of public goods and only weakly substitutable with other inputs.
Keywords: E22; E23; D20; 330